1997
DOI: 10.1071/r97005
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase regulation during embryonic implantation

Abstract: It has previously been demonstrated that uterine nitric oxide synthase (NOS) activity increases before embryonic implantation in rats. The aim of the present work was to investigate the regulation and the physiological relevance of the nitric oxide (NO) system in ovoimplantation. The increase in NOS activity in early pregnancy was found to be independent of the presence of embryos in the uterus. Whereas the Ca2+-dependent isoform of NOS increased gradually in the preimplantation days, the Ca2+-independent isof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 0 publications
1
26
1
Order By: Relevance
“…showed that decreased arginine and ornithine concentrations, combined with reduced activities of nitric oxide synthase and ornithine decarboxylase, resulted in reduced nitric oxide production and synthesis and concentrations of polyamines in the placenta and endometrium. Based on the current knowledge of the biological effects of nitric oxide and polyamines (Novaro et al, 1997;Sooranna et al, 1995;Wu et al, 2004), one could hypothesize that elevated synthesis of nitric oxide and polyamines enhanced endometrial and placental angiogenesis and growth during the early stage of pregnancy. Accordingly, Hazeleger et al (2007) reported that vascularization of the placenta at day 35 of gestation was greater in gilts offered daily 40 g of L-arginine from days 16 to 28 of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…showed that decreased arginine and ornithine concentrations, combined with reduced activities of nitric oxide synthase and ornithine decarboxylase, resulted in reduced nitric oxide production and synthesis and concentrations of polyamines in the placenta and endometrium. Based on the current knowledge of the biological effects of nitric oxide and polyamines (Novaro et al, 1997;Sooranna et al, 1995;Wu et al, 2004), one could hypothesize that elevated synthesis of nitric oxide and polyamines enhanced endometrial and placental angiogenesis and growth during the early stage of pregnancy. Accordingly, Hazeleger et al (2007) reported that vascularization of the placenta at day 35 of gestation was greater in gilts offered daily 40 g of L-arginine from days 16 to 28 of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Successful implantation of blastocyst is, in fact, due to the synchrony between the embryo development and the endometrial transformation into the decidua (an intense vascularized tissue that encapsulates the developing embryo). The factors responsible of the endometrial/decidual cell transformation are still poorly understood and seem to involve vasoactive agents such as prostaglandins, leukotrienes, platelet activating factor, and NO (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…These local modifications are fundamental for the generation of the decidual tissue and involve the production of vasoactive agents such as prostaglandins, leukotrienes, platelet activating factor, and NO (11)(12)(13)(14). A critical level of NO seems to be mandatory for the establishment of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of NO as a regulator of early developmental events has been established by studies that demonstrated that the oocyte and preimplantation embryo are exposed to NO, and oocyte maturation, preimplantation embryogenesis and implantation require NO (Biswas et al, 1998;Gagioti et al, 2000;Maul et al, 2003;Novaro et al, 1997;Purcell et al, 1999;Sengoku et al, 2001;Shukovski and Tsafriri, 1995;Telfer et al, 1995). Moreover, in vitro and in vivo studies showed that administration of either NOS inhibitors or NO donors hinders development of preimplantation embryos (i.e.…”
Section: Introductionmentioning
confidence: 99%